Pemanfaatan Instagram Sebagai Media Pemasaran Bagi Produk TempeAjah - Fernando, Wilsen; Rindiany; Oktarino, Hendra (Fakultas Komputer - Universitas Universal, 2022)
In this digital era, most business use social media to improve the relationship with consumers. One of the uses is in the field of marketing promotion.The objective of this research is to describe the use of social media Instagram as a promotion medium for TempeAjah in increasing the sales of Tempe. The researcher used qualitative descriptive case study methods and used interview technique to receive data. The results showed that the use of Instagram by TempeAjah was very effective because it was easy to advertise the products they sell.